Comparison Population of Rhyzopertha dominica (Coleoptera: Bostrichidae) and Damage Cereals During Storage Period - Hendrival Hendrival; Cut Rahmi; Yusnellis Yusnellis; Muhammad Yusuf N; Zurrahmi Wirda (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Storage of cereal is a section of the stage post-harvest and helpful for maintaining food availability against crop failures and natural disasters. The losses yield commodity cereal happened at the stage storage caused by Rhyzopertha dominica. This study aimed to determine the comparison population R. dominica and damage to rice and sorghum based on the storage period. The types of cereals used are rice and sorghum. The research was arranged in a completely randomized design (CRD) with the treatment of storage periods for rice and sorghum consisting of five levels is storage for 40, 60, 80, 100, and 120 days. Observation parameters included population R. dominica and damage as well increased moisture content of rice and sorghum. Data obtained from the observations were analyzed using analysis of variance. The results showed that the population of R. dominica and damage more happened to sorghum than rice based on the storage period. The storage period of 120 days could increase population R. dominica, damage and moisture content of rice and sorghum. Knowledge of the storage period for rice and sorghum give information so that not to stored rice and sorghum for long time periods